Bio-composites from Nicotiana tabacum stems waste: Exploring cellulose powder content and its impact on physical, mechanical, and thermal properties - Nasmi Herlina Sari; Emmy Dyah Sulistyowati; Suteja; Muhammad Zulfadli (Case Studies in Chemical and Environmental Engineering, 2025)
This study aims to develop and evaluate sustainable bio-composites using cellulose powder derived from Nicotiana tabacum stem waste, focusing on how varying filler content influences their structural, mechanical, and thermal properties. The cellulose powder was extracted through 5 % NaOH treatment and incorporated at various weight fractions to form composite formulations: BTN (10/90), BTL (15/85), BTK (20/80), BTI (25/75), BTH (30/70), and BTD (40/60), where the numbers represent the cellulose/resin ratio (% w/w). The composites were fabricated using hot press molding and evaluated for physical, mechanical, and thermal properties. Results showed that increasing cellulose content significantly enhanced performance. The highest tensile strength was achieved at 159.47 ± 11.49 MPa for the BTD composite (40 % cellulose), representing a substantial improvement over lower filler loadings. Flexural strength similarly peaked at 174.92 ± 8.9 MPa, and thermal stability increased, with a decomposition onset near 380 °C. FTIR analysis confirmed the presence of cellulose-related functional groups and improved interfacial bonding, while SEM images revealed reduced voids and better dispersion at higher filler contents. The wear resistance also improved, with the lowest wear rate of 0.073 mm3/Nm observed for BTD. These findings underscore the potential of Nicotiana tabacum-based composites as eco-friendly materials for structural and thermal applications.